Pengaruh Motivasi Binge-Watching Netflix terhadap Behavioral Involvement - Novianty, Melinda; Sari, Wulan Purnama (Koneksi, 2023)
The ongoing pandemic makes people binge-watch. Binge watching is watching several episodes or hours of the same television series or film in a row. Often with the intention of finishing a TV series, or TV shows quickly. This phenomenon has just become a trend due to the development of technology and to fill spare time during WFH. One of the video-on-demand platforms that provides binge-watching is Netflix. Therefore, the researcher chose the topic of the influence of binge watching motivation on Netflix on behavioral involvement. The research using uses & gratification theory aims to measure how much motivation and satisfaction affect binge-watching behavior. The approach uses a quantitative approach. Sampling technique using Non-Probability Sampling. The method of collecting data is through a questionnaire. The total respondents in the study amounted to 130 people. The population in this study is the Gen-Z audience aged 9-26 years. The study found the Pearson correlation value that there is a significant relationship between the influence that motivates Netflix binge-watching Gen-Z audiences of 0.700 on behavioral involvement. While the coefficient value shows that there is a correlation of 49.0% the motivating influence of binge-watching on behavioral involvement. Pandemi yang berkelanjutan membuat khalayak melakukan binge-watching. Binge watching adalah menonton beberapa episode atau jam dari serial televisi (TV Series) atau film yang sama berturut-turut. Seringkali dengan maksud untuk menyelesaikan TV series, atau TV shows dengan cepat. Fenomena ini baru saja menjadi tren karena berkembangnya teknologi serta mengisi waktu luang semasa bekerja dari rumah (work from home) selama pandemic Covid19. Salah satu platform video-on-demand yang menyediakan sarana binge-watching adalah Netflix. Peneliti memilih topik pengaruh motivasi binge-watching pada Netflix terhadap behavioral involvement. Penelitian menggunakan teori uses & gratification bertujuan untuk mengukur seberapa besar motivasi dan kepuasan berpengaruh terhadap perilaku bingewatching. Pendekatan menggunakan pendekatan kuantitatif. Teknik pengambilan sampel menggunakan Non-Probability Sampling. Metode pengumpulan data melalui kuisioner. Total responden dalam penelitian berjumlah 130 orang. Populasi dalam penelitian adalah khalayak Gen-Z yang berusia 9-26 tahun. Penelitian menemukan nilai pearson correlation bahwa terdapat hubungan signifikan diantara pengaruh yang memotivasi binge-watching Netflix audiens Gen-Z sebesar 0,700 terhadap behavioral involvement. Sedangkan nilai koefisien menujukkan terdapat korelasi sebesar 49.0% pengaruh yang memotivasi binge-watching terhadap behavioral involvement.